MEDIA SOSIAL SEBAGAI KONTEKS PENDIDIKAN KRISTIANI KONTEKSTUAL BAGI GENERASI MILLENNIAL - Apriani Magdalena Sibarani (Universitas Methodist Indonesia, 2020)
The advancement of science and technology plays a big role in the development of our society. The backlog in education can be calibrated through social media. As social media and millenials are inseparable, it is but proper to make use of social media as an effective platform to curb the millenials’ Christian Education illiteracy. This article explores the utilitization of social media as a double-edged tool to deliver a holistic Christian Education context right at their comfort. This article recommends Shared Christian Praxis (SCP) approach as a method to tailor Christian Education context for millennials in social media context.